2018
DOI: 10.1007/s00436-018-5931-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Ascaris lumbricoides and Ascaris suum recovered from humans and pigs in Thailand, Lao PDR, and Myanmar

Abstract: Ascaris lumbricoides is the largest roundworm known from the human intestine while Ascaris suum is an internal parasite of pigs. Ascariasis, caused by Ascaris lumbricoides, has a worldwide distribution. Here, we have provided the first molecular identification of Ascaris eggs and adults recovered from humans and pigs in Thailand, Lao PDR, and Myanmar. We amplified and sequenced nuclear ribosomal DNA (ITS1 and ITS2 regions) and mitochondrial DNA (cox1 gene). Sequence chromatograms of PCR-amplified ITS1 region r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
6
21
1
Order By: Relevance
“…suum samples from Brazil. The number of different cox 1 haplotypes obtained in this study– 17 haplotypes to cox 1 and 32 haplotypes to nad 1 –is similar to that found in previous studies in Asia and Africa [32,35]. Although some localities present low prevalence, these results suggest that there is raised cox 1 genetic diversity in Ascaris across Brazil.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…suum samples from Brazil. The number of different cox 1 haplotypes obtained in this study– 17 haplotypes to cox 1 and 32 haplotypes to nad 1 –is similar to that found in previous studies in Asia and Africa [32,35]. Although some localities present low prevalence, these results suggest that there is raised cox 1 genetic diversity in Ascaris across Brazil.…”
Section: Discussionsupporting
confidence: 89%
“…The ML tree and MJ network analysis based in both cox 1 and nad 1 revealed three main clusters (A-C). Several studies demonstrate this topology for Ascaris mitochondrial targets, in which two main groups are formed with i) clusters A and C; and ii) cluster B [34,35]. Our main finding is that, despite this division, there is no separation between specimens obtained from humans and from pigs, presumably A .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This methodology could assist the clinical method for diagnosis of ascariasis, in particular at the diagnostic stage (eggs) rather than infectious stage (juveniles). Compared with prior reports on detection of species 41,52 , the present study clearly distinguishes the species of nematodes with 90% certainty. To the best of our knowledge, there is no similar report on identification of species of nematodes through their lifetime measurements.…”
Section: Further Identification Of Nematode Eggs -Lifetime Measuremensupporting
confidence: 42%
“…Population genetic studies of A. lumbricoides have drawn varying conclusions about whether zoonotic transmission is frequent ( Anderson and Jaenike, 1997 ; Dutto and Petrosillo, 2013 ; Nejsum et al, 2012 ; Nejsum et al, 2005a ). Some studies have shown that cross-species transmission occurs between pigs and humans living in close proximity ( Anderson, 1995 ; Betson et al, 2014 ; Miller et al, 2015 ; Monteiro et al, 2019 ; Nejsum et al, 2005b ; Peng and Criscione, 2012 ; Sadaow et al, 2018 ; Takata, 1951 ; Zhu et al, 1999 ). This is especially common in non-endemic regions, probably because zoonotic transmission is less likely to be identified in areas where human-to-human transmission is common.…”
Section: Introductionmentioning
confidence: 99%